ISLAMIC MORAL ECONOMY IN TRANSITION: THE SHIFT FROM RELIGIOUS ETHICS TO MARKET MORALITY IN INDONESIA’S HALAL INDUSTRY - Subambang Harsono; Zuhrinal M. Nawawi (International Journal of Cultural and Social Science, 2026)
The halal lifestyle phenomenon in Indonesia reflects social, cultural, economic, and spiritual shifts within urban Muslim communities. This study analyzes how pious values are commodified and consumed within capitalist modernity. Using an interpretive qualitative approach with cultural ethnography, the study includes interviews, participant observation, and digital discourse analysis of halal industry actors, middle-class Muslim consumers, and the hijrah community in Medan, Deli Serdang, and Binjai. Reflexive thematic analysis and Critical Discourse Analysis (CDA) uncover the dynamics of meaning, symbols, and ideology in halal consumption. The findings reveal three key points: (1) the commodification of piety as an economic asset; (2) performative Muslim identity through digital media; and (3) the shift from Islamic moral economy to moral capitalism. This study offers an interdisciplinary perspective on halal lifestyle as both a consumption practice and an ideological discourse that negotiates spirituality, identity, and capitalism, contributing to the development of Islamic consumer culture and ethical business practices.